Thymus alterations and susceptibility to immune checkpoint inhibitor myocarditis - Fenioux, Charlotte; Abbar, Baptiste; Boussouar, Samia; Bretagne, Marie; Power, John R.; Moslehi, Javid J.; Gougis, Paul; Amelin, Damien; Dechartres, Agnès; Lehmann, Lorenz; Courand, Pierre-Yves; Cautela, Jennifer; et al. (Nature medicine, 2023)
Immune checkpoint inhibitors (ICI) have transformed the therapeutic landscape in oncology. However, ICI can induce uncommon life-threatening autoimmune T-cell-mediated myotoxicities, including myocarditis and myositis. The thymus plays a critical role in T cell maturation. Here we demonstrate that thymic alterations are associated with increased incidence and severity of ICI myotoxicities. First, using the international pharmacovigilance database VigiBase, the Assistance Publique Hôpitaux de Paris-Sorbonne University data warehouse (Paris, France) and a meta-analysis of clinical trials, we show that ICI treatment of thymic epithelial tumors (TET, and particularly thymoma) was more frequently associated with ICI myotoxicities than other ICI-treated cancers. Second, in an international ICI myocarditis registry, we established that myocarditis occurred earlier after ICI initiation in patients with TET (including active or prior history of TET) compared to other cancers and was more severe in terms of life-threatening arrythmias and concurrent myositis, leading to respiratory muscle failure and death. Lastly, we show that presence of anti-acetylcholine-receptor antibodies (a biological proxy of thymic-associated autoimmunity) was more prevalent in patients with ICI myocarditis than in ICI-treated control patients. Altogether, our results highlight that thymic alterations are associated with incidence and seriousness of ICI myotoxicities. Clinico-radio-biological workup evaluating the thymus may help in predicting ICI myotoxicities.
Gesehen am 17.04.2024